Radon, an invisible killer in Canadian homes: perceptions of Ottawa-Gatineau residents - Khan, Selim; Krewski, Daniel; James, Gomes; Deonandan, Raywat (Université d'Ottawa | University of Ottawa, 2018)
Objectives Canadians have reason to care about indoor air quality as they spend over 90% of the time indoors. Although indoor radon causes more deaths than any other environmental hazard, only 55% of Canadians have heard of it, and of these, 6% have taken action. The gap between residents’ risk awareness and adoption of actual protective behaviour presents a challenge to public health practitioners. Residents’ perception of the risk should inform health communication that targets motivation for action. In Canada, research about the public perception of radon health risk is lacking. The aim of this study was to describe residents’ perceptions of radon health risks and, applying a theoretical lens, evaluate how perceptions correlate with protection behaviours. Methods We conducted a mixed online and face-to-face survey (N = 557)with both homeowners and tenants inOttawa-Gatineau census metropolitan area. Descriptive, correlation, and regression analyses addressed the research questions. Results Compared to the gravity of the risk, public perception remained low. While 32% of residents expressed some concern about radon health risk, 12% of them tested and only 3% mitigated their homes for radon. Residents’ perceptions of the probability and severity of the risk, social influence, care for children, and smoking in home correlated significantly with their intention to test; these factors also predicted their behaviours for testing and mitigation. Conclusion Health risk communication programs need to consider the affective aspects of risk perception in addition to rational cognition to improve protection behaviours. A qualitative study can explore the reasons behind the gap between testing and mitigation.
Keywords: Air pollution; Indoor; Radon; Risk; Perception; Canada